PERBANDINGAN NAIVE BAYES DAN C45 DALAM KLASIFIKASI TES KESEHATAN MAHASISWA BARU AKBID AS-SYIFA - Sembiring, Feby Wulandari; Handoko, Wiwin; Batu Bara, Firdha Agis Utami; Sulaseh, Sulaseh (LPPM STMIK Royal Kisaran, 2022)
Abstract: Medical test is important to determine the health of a person's body so they are often carried out and have even become one of the requirements for an institution to accept new members such as the As-Syifa Midwifery Academy which conducts medical tests for prospective new students. The problem is that so far the classification system for recapitulation of medical test results is still done manually, thus slowing the performance of the campus and it is feared that there will be damage to the data format. The problem solving technique above is carried out with a data mining process using Naïve Bayes and Decision Tree C45 where the two algorithms are compared to find the 1 best classification algorithm to be implemented in the system. The dataset uses data on the recapitulation of the results of the 2018 new student health tests sourced from the Administration (TU) of Akbid As-Syifa. The comparison uses 4 data testing models and the confusion matrix as the performance evaluation value of the modeling algorithm. The modeling results obtained that the Decision Tree C45 algorithm is superior and suitable to be implemented with an accuracy rate of 100% while Naïve Bayes has a maximum accuracy rate of 96%. The purpose of this study was to help Akbid As-Syifa classify the results of the health test of prospective new students. Keywords: Medical test; Prospective new students; Naïve Bayes; C45. Abstrak: Tes kesehatan merupakan hal penting untuk mengetahui kesehatan tubuh seseorang sehingga banyak dilakukan bahkan telah menjadi salah satu persyaratan bagi sebuah lembaga untuk menerima anggota baru seperti halnya Akademi Kebidanan (Akbid) As-syifa yang melakukan tes kesehatan bagi calon mahasiswa baru. Permasalahannya selama ini sistem klasifikasi rekapitulasi hasil tes kesehatan masih dilakukan secara manual sehingga memperlambat kinerja pihak kampus serta dikhawatirkan adanya kerusakan format data. Adapun teknik penyelesaian masalah diatas dilakukan dengan proses data mining menggunakan Naïve Bayes dan Decision Tree C45 dimana kedua algoritma tersebut dibandingkan untuk mencari 1 algoritma klasifikasi terbaik unutk diimplementasikan dalam sistem. Dataset menggunakan data rekapitulasi hasil tes kesehatan calon mahasiswa baru tahun 2018 bersumber dari Tata Usaha (TU) Akbid As-syifa. Perbandingan menggunakan 4 model pengujian data dan confusion matrix sebagai nilai evaluasi performa dari pemodelan algoritma tersebut. Hasil pemodelan diperoleh algoritma Decision Tree C45 lebih unggul dan cocok untuk diimplementasikan dengan tingkat akurasi 100% sedangkan Naïve Bayes tingkat akurasinya maksimal sebesar 96%. Tujuan penelitian ini adalah membantu pihak Akbid As-syifa mengklasifikasikan hasil tes kesehatan calon mahasiswa baru. Kata Kunci: Tes kesehatan; Calon Mahasiswa Baru; Naïve Bayes; C45.